Assessment competence in Indonesian language learning of rural primary school teachers - Sumarwati, Sumarwati; Anindyarini, Atikah; Suryanto, Edy; Hadiyah, Hadiyah; Menjamin, Sumaiyah (Universitas Ahmad Dahlan, 2023)
This study aims to examine the vulnerability of primary school teachers in rural areas in conducting authentic and integrative assessments of Indonesian language learning. This research approach is a case study. The participants were 50 primary school teachers grade 5 in rural areas. Data were obtained through questionnaires, teacher-made assessment instruments, and interviews. Data were analyzed quantitatively and qualitatively. The results showed that most of the teachers did not understand the concept of authentic and integrative assessment in learning Indonesian. However, from an analysis of the assessment instrument he made, the teacher has applied the concept of authentic and integrative assessment because he copied from the teacher's book provided by the government. In practice, most teachers apply authentic and integrative assessment to receptive language skills (reading and listening), but only a small number apply them to productive skills (writing and speaking). The reason is insufficient time, the description of the score has ambiguous meaning, and the facilities at the school are not supportive. It is urgent to hold periodic training for teachers in rural areas to improve competence in assessing Indonesian subjects so that they no longer use the teacher's book as the only source of learning, including in assessment.